Break your glass slippers - Lovelace, Amanda (The you are your own fairy tale series, 2020)
"Amanda Lovelace, the bestselling & award-winning author of the 'Women are some kind of magic' poetry series, presents a new companion series, 'You are your own fairy tale.' [This] first installment ... is about overcoming those who don't see your worth, even if that person is sometimes yourself. In the epic tale of your life, you are the most important character, while everyone is but a forgotten footnote--even the prince"--